Nano-Sized PtRu/C Electrocatalyst With Separated Phases and High Dispersion Improves Electrochemical Performance of Hydrogen Oxidation Reaction - Feng, Yiling; Han, Wei; Wang, Tingyu; Chen, Qian; Zhang, Yan; Sun, Yonggang; Zhang, Xin; Yang, Lin; Chen, Song; Xu, YuXiang; Tang, Hong; Zhang, Bing; et al. (Frontiers in Chemistry, 2022)
Alloys and core-shell nanoparticles have recently received enormous attention, and opened up new avenues for highly active catalysts. Despite considerable advances in this field, the majority of proposed approaches suffer from either complicated procedures or unstable structure, severely hindering their practical applications. Here, we successfully synthesized alloy electrocatalyst with separated phases, PtRu alloy nanoparticles robustly supported by carbon matrix (PtRu/C), using a convenient two-step solvothermal method. The constructed PtRu/C at different NaOH contents (0~1.25 mmol) were compared and electrochemical activity were evaluated by the hydrogen oxidation reaction (HOR). The homogeneous distribution and smallest average size of Ru and Pt nanoparticles on the carbon by comparison, appeared at approximately 4 nm, proved that PtRu/C-0.75 possessed abundant accessible active sites. The catalytic activities and the reaction mechanism were studied via electrochemical techniques. The unique electronic structure and efficient charge transfer at the interfaces of PtRu/C-0.75, resulting in the excellent activity with the largest j0 value of 3.68 mA cm-2 in the HOR.